Synthesis, characterization and optimization of magnetic nanostructures by sol-gel technique and application in water purification - Syed Farhan, Hasany (2014)
Tailored maghemite nanoparticles with improved thermo-physical properties have attracted vast interest in current years. The design and synthesis of these particles have generated innovative magnetic, optical and other physical properties that arise from quantum size effect and enhanced surface to volume ratio with huge application significance. Tailored magnetic nanoparticles are prepared either by wet chemical methods such as colloidal chemistry or by dry processes such as vapor deposition techniques. This PhD project, aimed to develop novel vanadium doped maghemite (Fe2−xVxO3) particles with novel properties of ~ 5 nm and nanohybrids of maghemite size ranges from 13-15 nm decorated multiwalled carbon nanotubes (MWCNTs) by wet methods. Tailored maghemite – MWCNTs nanohybrid was later, applied in efficient Lead removal application from aqueous solutions. The synthesis involved a facile Sol-gel route, with control over the size, morphology and the magnetic properties. Tailored maghemite particles were synthesized from a metal precursors and MWCNTs in a single pot reactor assembly, with forced nucleation in slight basic medium at pH ~ 9, yields crystalline, pure phase and thermally stable particles and nanohybrids. The synthesized particles and nanohybrids were characterized for different physical properties; crystallinity, phase purity and transformations, morphology, hydrodynamic particle size, polydispersity, magnetic properties, surface area studies, elemental and oxidation states of iron and vanadium, thermal stability, colloidal stability, zeta potential values and elemental ratios of iron, oxygen and carbon in tailored maghemite – MWCNT nanohybrids. The comparative changes in structural, magnetic, surface area and colloidal properties of the nanoparticles were found significant for future applications in nano devices, magnetic coatings, magnetic separations and other applications. Tailored maghemite – MWCNT nanohybrids were applied for efficient removal of Lead from aqueous solutions in batches magnetically. Lead adsorption mechanism was studied with Kinetics rate, adsorption isotherms. The effects of pH, contact time, adsorbent dosage, and agitation speed on the Pb (II) removal were scrutinized. Repeated adsorption–desorption cycles were studied to investigate the prolonged use of nanohybrids. The maximum removal achieved was ~ 94 % in less than 2 h in a pH range of 6–7, which is very good yield with respect to previous studies. A mathematical model (Minitab version 15) was studied to validate the experimental method for the removal of Lead